Geographic variation in bone carbonate and water δ18O values in Mendoza, Argentina and their relationship to prehistoric economy and settlement - Ugan, Andrew (2012)
Questions of mobility, settlement pattern, and their relation to economic organization and resource use are central to ongoing work in central-western Argentina. Here we analyze geographic patterns in the distribution of 178 human bone carbonate δ18O samples, 46 human tooth enamel carbonate δ18O samples, and 48 water δ18O samples from throughout the Andean Cordillera and Monte Desert and evaluate their implications for prehistoric mobility and economy. We confirm and refine previous generalizations regarding a highland/lowland dichotomy in water δ18O values and show that the range of human carbonate δ18O values generally reflect available water sources. While there is little within-lifetime change in patterns of water use, we show that most individuals have stable isotope signatures consistent with water use from multiple areas or areas other than where they were ultimately interred. These data indicate high levels of residential mobility, and we conclude by discussing their implications for our understanding of regional prehistory. © 2012 Elsevier Ltd.